2016
DOI: 10.1002/cphc.201600271
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Adsorption of Halide Ions on Graphene Materials

Abstract: Graphene has recently found applications in a wide range of fields. Density functional calculations show that halide ions can be adsorbed on pristine graphene, but only F(-) has an appreciable binding energy (-97.0 kJ mol(-1) ). Graphene materials, which are mainly electron donors, can be made strong electron acceptors by edge functionalization with F atoms. The binding strengths of halide ions are greatly enhanced by edge functionalization and show direct proportionality with the degree of functionalization Θ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…at the BLYP/LANL2DZ level. For Cl − , we found that the interaction energies obtained in our work were smaller than the previous results ,. This is probably attributed to the larger cluster size (C 150 H 30 ) adopted in our computation.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…at the BLYP/LANL2DZ level. For Cl − , we found that the interaction energies obtained in our work were smaller than the previous results ,. This is probably attributed to the larger cluster size (C 150 H 30 ) adopted in our computation.…”
Section: Resultscontrasting
confidence: 78%
“…have proved that anion‐graphene interactions are unexpectedly strong and they attributed this phenomenon to the strong electron‐accepting ability of the unoccupied π*‐orbital. Zhu et al . showed that halide ions can remain stable on graphene surface, because the graphene acts as an acceptor by accepting the electron from halide ions.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that our results are surprisingly insensitive to varying the flexibility of graphene but that ΔΔG ads does depend on the choice of interaction strength between the ion and the graphene. We have chosen this interaction to reproduce the experimental free energy difference, which yields an adsorption energy for iodide at graphene in vacuum (no waters) in reasonable agreement with density functional theory (21,22). This is similar in spirit to the approach of Williams et al (23), who capture the effects of the graphene-ion polarization interaction (as measured by density functional theory calculations) by empirically adjusting the interaction strength between the ion and the carbon atoms.…”
Section: Significancementioning
confidence: 87%
“…Biochar, produced by the pyrolysis of biomass, has proven to be effective to improve soil properties, remediate soils with heave metal and organic pollutants and increase crop biomass [19]. With use of density functional calculations, we have demonstrated that biochar is potential to remediate soils with anionic pollutants [20], in addition to heavy metal ions that are known to us all.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [20] and Shi et al [59] clearly show that halide ions are potentially adsorbed on graphene, where halide ions are electron donors while graphene turn to be electron acceptors. Zhu et al [20] demonstrate the binding strengths of metal ions on pristine graphene are stronger than the halide ion when they are adsorbed; however, the edgefluorination alters the adsorption priority of metal ions versus halide ions and the adsorption strengths of metal ions/anions change in direct/reverse proportion with increase in functionalization degrees. In consequence, the preferential adsorption and selective removal of certain metal ions or anions can be facilely realized by choice of an appropriate functionalization degree.…”
Section: +mentioning
confidence: 99%